Policies, Prices, and Poverty : The Sugar, Vegetable Oil, and Flour Industries in Senegal - Mbaye, Ahmadou Aly; Golub, Stephen S.; English, Philip (World Bank, Washington, DC, 2015)
Like many countries in Sub-Saharan Africa, Senegal has struggled to develop its industrial sector in the face of import competition. For basic food products, there is an implicit trade-off between the objectives of maintaining employment and lowering the cost of living, both of which figure prominently in current government policy. Conflicting pressures have led to a rather inconsistent policy mix of high levels of protection with price ceilings. The products of the three industries examined here—sugar, vegetable oil, and flour—account for roughly 14 percent of the consumption basket of the poor, so distortions in their prices can have a significant effect on poverty reduction. This paper compares domestic prices in Senegal with world prices since 2000, and then explains the difference by examining the protection enjoyed by these industries, along with their market structure. The analysis finds that high protection and market power have resulted in domestic prices which were often two or three times the equivalent world price. Tightening of price ceilings and some liberalization have taken place recently, but consumers have continued to pay above world prices for sugar and edible oil in 2014. The paper estimates that if this differential were eliminated, the purchasing power of households around the poverty line would increase by 3 percent, 227,000 people would move above the poverty line, and the national poverty rate would drop by 1.9 percentage points. The cost to consumers far exceeds the total wage bill paid by these industries. Further liberalization of these industries is recommended, along with phasing out price controls and shifting government policy from protecting traditional enterprises to the promotion of new export-oriented ones.